Establishing cyber court in Malaysia / Nissa Hasana Lokman Hakim, Nur Hidayah Che Hat and Intan Shahirah Ahmad Zulkunain - Lokman Hakim, Nissa Hasana; Che Hat, Nur Hidayah; Ahmad Zulkunain, Intan Shahirah (2014)
Cyber crime is a phenomenon that is undoubtedly rampant in Malaysia. The pandemic of cyber crime has not only affecting the nation's economic and the public at large, it also overloads the traditional judiciary with cyber crime cases. At present, all criminal matters are treated under the same criminal division. However, it is important to realize that cyber-based crimes do not operate the same with the traditional criminal cases by virtue of the information superhighway and the high technological advances. Furthermore, cyber crime is a fast-growing area of crime and the number of Internet users is increasing from day to day. Subsequently, more and more criminals are exploiting the speed, convenience and anonymity of the Internet to commit a diverse range of criminal activities that know no borders, either physical or virtual. Thus, this paper shall highlight on the needs and urgency to establish a specialized court for cyber cases, especially on cyber crime matters, from there, this research shall analyze the initiatives taken at the international level and also in India especially on the country's establishment of the Cyber Appellate Tribunal (CAT). This analysis is carried out in order to study the rationale behind the initiatives taken from foreign entities and therefore, thorough evaluation can be made in favor of the prospective cyber court in Malaysia by taking into consideration insights from local experts pertaining to this matter.